Faculty Development Series on Assessment in Graduate Medical Education: Interpersonal and Communication Skills - Kathleen Bartlett; Sybil Pentsil; Betty Ansong-Assoku; Suzanne Woods (Association of American Medical Colleges, 2013)
Abstract Introduction This resource is a set of PowerPoint slides that were designed for the purpose of faculty development. The slides are intended for presentation by a residency program director (or designee) in a didactic or workshop setting for the purpose of enhancing the faculty's ability to assess interpersonal and communication skills in trainees. Methods This case-based presentation begins by defining the competency of interpersonal and communication skills, then explores various assessment tools available for evaluating learners in this competency. The presentation introduces the concept of The Pediatrics Milestone Project and demonstrates how Milestones can be used to better assess interpersonal and communication skills. The presentation concludes with a series of case studies where the participants are asked to assess the performance of the learners in the case studies. Results This presentation has been presented by two of the authors to their own faculty. The presentations were well-received in each setting generating robust discussion. Faculty expressed improved understanding of the competency, assessment tools, and the Pediatric Milestones. Discussion The interactive nature of the presentation could be improved by using high-quality videos that demonstrate interpersonal and communication skills. The content of this resource is specific to the specialty of pediatrics with regards to the cases and the Milestones. It could be adapted to other specialties by modifying the cases slightly and eliminating or substituting specialty-specific Milestones. Although this presentation was designed for graduate medical education, it can be easily adapted to undergraduate medical education.